2019
DOI: 10.5194/bg-16-275-2019
|View full text |Cite
|
Sign up to set email alerts
|

Varying relationships between fire radiative power and fire size at a global scale

Abstract: Abstract. Vegetation fires are an important process in the Earth system. Fire intensity locally impacts fuel consumption, damage to the vegetation, chemical composition of fire emissions and also how fires spread across landscapes. It has been observed that fire occurrence, defined as the frequency of active fires detected by the MODIS sensor, is related to intensity with a hump-shaped empirical relation, meaning that occurrence reaches a maximum at intermediate fire intensity. Raw burned area products obtaine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 71 publications
1
26
0
Order By: Relevance
“…Other than CRB incidences, the radiant heat output, i.e. fire intensity from each event, is also an important parameter ( Laurent et al., 2019 ). Therefore, the parameter FRP is helpful to estimate the pixel-integrated FRP (in megawatts; MW).…”
Section: Resultsmentioning
confidence: 99%
“…Other than CRB incidences, the radiant heat output, i.e. fire intensity from each event, is also an important parameter ( Laurent et al., 2019 ). Therefore, the parameter FRP is helpful to estimate the pixel-integrated FRP (in megawatts; MW).…”
Section: Resultsmentioning
confidence: 99%
“…A global review of fire intensities by Laurent et al (2019) based on remote sensing data indicated that the largest and most intense fires occur in Australia, the grasslands of Kazakhstan, Namibia, the Sahel and Patagonia. High intensity fires also occur in the forested areas of the western United States and Boreal North America.…”
Section: Resultsmentioning
confidence: 99%
“…YHR, the major wheat-producing area in China, is located in the vast flat plain in eastern China. Figure 1a shows the daily number of satellite fire counts in YHR, where cropland, especially wheat, dominates the vegetation cover (Gong et al, 2019;Lei and Yuan, 2013;Van Der Werf et al, 2010). The limited duration of agricultural fire combined with the low temporal resolution of MODIS may increase the difficulty of signal capture and lead to underestimation of fire counts Song, 2009, 2010;Giglio et al, 2009;Randerson et al, 2012;Yin et al, 2019).…”
Section: Fire-induced Surface Albedo Changementioning
confidence: 99%
“…The most concentrated area of burning in eastern China is the Yellow-Huai River area (YHR), which connects the middle and lower reaches of the Yellow River and Yangtze River. YHR is the major wheat-producing area in China (Lei and Yuan, 2013). An extremely typical pollution episode was triggered by BB emissions from YHR in June 2012, during which a yellow haze blanketed the Yangtze River Delta (YRD) (Ding et al, 2013a;Huang et al, 2012b;Xie et al, 2015).…”
Section: Introductionmentioning
confidence: 99%